Ten Years of Transformation : Macroeconomic Lessons - Wyplosz, Charles (World Bank, Washington, DC, 2015)
After surveying the facts and distilling the voluminous literature on the transition to market economies, the author arrives at several conclusions: with hindsight, the old debate - Big Bang versus gradualism - was really a problem of feasibility, although many of the arguments in favor of the Big Bang have now been proven right. Once more, inflation has been found to be incompatible with growth and the importance of a good microeconomic structure - especially an effective banking system - has been confirmed. The decline of the state in transition economies is both spectacular and puzzling - combining features that are both desirable and dangerous. Among useful lessons learned: 1) It has paid to start early and move fast. The Big Bang is highly desirable but impractical, and gradualism is unavoidable but ought to be compressed as much as possible. The countries that bit the bullet early and hard have done better over the past decade. 2) Stabilize first; growth next. Macroeconomic stabilization is a prerequisite for growth. The budget deficit need not be eliminated, but the link between deficits and money growth must be severed. 3) Structural reform is important, and microeconomic policies, often overlooked, should be started as soon as possible. This means establishing property rights, hardening budget constraints, building a healthy banking system, and ensuring true domestic competition. 4) The choice of an exchange rate regime, another early controversy, is apparently less important than adherence to a strict monetary policy. The floaters have tightly managed their exchange rates, while the fixers have repeatedly devalued and have often ended up floating. Some form of monetary targeting is needed, but it matters little which target is chosen so long as it is adhered to. 5) Creating irreversibilities early on allows governments to change without seriously affecting the transition. The less stable the economy, the more politics matters. A shaky economic basis is fertile ground for policy reversals that set the clock back several years (Bulgaria, Romania, Russia).